CSR profiles and innovation in Italian agri-food firms. (15th October 2022) - Coppola, A.; Cozzi, M.; Romano, S.; Viccaro, M.
Abstract: New business models that integrate sustainability into corporate strategies and combine environmental, economic, and social issues with production practices are on the rise. Implementation of corporate social responsibility (CSR) initiatives may trigger organizational, process, and product changes, thus affecting a firm's innovation pattern. This study explores the relationship between CSR and innovation by considering the multidimensional nature of these concepts and taking account of all components of CSR and different types of innovation. Therefore, our work aims to verify whether the link between CSR and innovation depends on the CSR pattern and whether firms with specific CSR behaviour differ in terms of innovativeness and type of innovation. The analysis refers to Italian agri-food firms and is based on microdata from the first Permanent Business Census carried out by the National Institute of Statistics (ISTAT). Our results support a positive relationship between the intensity of CSR dimensions and the implementation of innovation projects, and between specific strategies of social responsibility and innovation. Indeed, the greatest effects on innovation are associated with initiatives aimed at collective and territorial interests, but a relevant effect is also related to more diversified CSR strategies that merge social and environmental actions. This demonstrates the synergistic effect of different CSR practices in fostering innovation. Moreover, CSR activates a change in a firm's organisation that simultaneously affects procedures, processes, and products. Highlights: The likelihood to innovate increases when the firm undertakes CSR actions. Different CSR profiles activate specific innovation patterns. The integration of CSR in the firm's strategy enhances the link between CSR profiles and innovation. Diversified CSR strategies have a synergistic effect in fostering innovation compared to strategies focused on a single CSR dimension.